Cost engineering: why, what and how? - Roy, Rajkumar (Cranfield University, 2003)
Cost has become a major business driver in many industries. It is observed that there is a lack of understanding about the process to estimate, manage and control costs across the lifecycle of a product. This report presents a business case to understand the principles of ‘Cost Engineering’ within the manufacturing industries. The main focus of the report is in the techniques and tools used in cost estimating – one of the major activities in cost engineering. Five different methods of cost estimating are discussed in the report along with cost management issues including risk analysis. The report also presents research findings on ‘industry practice’ in hardware and software development cost estimating. The study shows the lack of research in hardware cost estimating and highlights the lack of communication within different groups of people involved in cost engineering. The report then focuses on the research trends in cost engineering and presents two case studies from recent research projects at Cranfield University. The case studies clearly show the progress in formalising the cost engineering process and the improvements in the current understanding about the domain. Two major areas of research as identified in the report are: i) integrating the cost engineering capability with the ERP (enterprise resource planning) environment so that data can be shared effectively, and ii) capture and reuse of human expertise in cost engineering for performance improvement. Finally, the report also identifies the need for simpler and cheaper cost engineering software for Small and Medium scale Enterpris
Keywords: Cost engineering; Cost estimating; Cost management; Cost modelling; DEG report